Reaksi Merugikan Obat Kanker Berbasis Antrasiklin pada Pasien Kanker Payudara di RS Kanker Dharmais - Chairunnisa, Dian Fitri; Harahap, Yahdiana; Syafhan, Nadia Farhanah; Purwanto, Denni Joko (Pengurus Pusat Ikatan Apoteker Indonesia, 2024)
Breast cancer is the type of cancer that most often affects women worldwide. Doxorubicin is an anthracycline class, a first-line anticancer therapy with clinical activity in breast cancer. Doxorubicin can cause cardiotoxic effects due to the formation of doxorubicinol as its primary metabolite. Adverse drug reactions also vary depending on the chemotherapy regimen. This study aimed to determine the adverse reactions to anthracycline-based drugs that breast cancer patients often experience. This observational descriptive study was conducted from April to July 2022 at the Dharmais Cancer Hospital, Jakarta. The sample in this study was breast cancer patients undergoing chemotherapy with anthracycline-based regimens. Data were collected through interviews and observation of medical records, which were analyzed by univariate analysis. The results showed that the most frequent drug reaction was alopecia, with a percentage of 97.1%. They were followed by nausea at 85.7%, vomiting at 71.4% and pain at 65.7%. The fastest time for nausea to appear is within 18-24 hours (peak days 2 to 3) after chemotherapy. Did not experience a decrease in left ventricular ejection fraction by 34.3%, and 65.7% experienced a reduction in left ventricular ejection fraction after doxorubicin chemotherapy. Patients who underwent a reduction in left ventricular ejection fraction after doxorubicin chemotherapy had a decrease in ejection fraction <10%, and no patients experienced a decline in left ventricular ejection fraction >10%. Breast cancer patients who receive anthracycline-based treatment can experience adverse drug reactions, including nausea, vomiting, alopecia, pain and decreased left ventricular ejection fraction.